Chondrocalcinosis of the Knee and the Risk of Osteoarthritis Progression: Data From the Knee and Hip Osteoarthritis Long‐term Assessment Cohort. Issue 5 (3rd April 2020) - Latourte, Augustin; Rat, Anne‐Christine; Ngueyon Sime, Willy; Ea, Hang‐Korng; Bardin, Thomas; Mazières, Bernard; Roux, Christian; Guillemin, Francis; Richette, Pascal
Abstract : Objective: To assess the impact of knee chondrocalcinosis (CC) on the 5‐year risk of joint replacement and disease progression in patients with knee osteoarthritis (OA). Methods: Patients with symptomatic knee OA without previous total joint (knee or hip) replacement (TJR) were recruited from the Knee and Hip Osteoarthritis Long‐term Assessment cohort. Cox proportional hazards regression and generalized estimating equation models were used to compare the time from inclusion or OA diagnosis to total knee replacement (TKR) or TJR between patients with and those without knee CC at inclusion. In patients without incident TKR, logistic regression was performed to examine the association between CC and radiographic progression (Kellgren/Lawrence [K/L] grade) or worsening of Western Ontario and McMaster Universities Arthritis Index (WOMAC) subscores for OA pain or function between years 0 and 5. Hazard ratios (HRs) and 95% confidence intervals (95% CIs) were estimated. Analyses were adjusted for age, sex, body mass index, WOMAC subscores, and K/L grade. Results: Among the 656 patients included, 93 (14.2%) had knee CC, and 91 (13.9%) underwent TKR during the follow‐up. Risk of TKR was not affected by the presence of knee CC (HR 1.26 [95% CI 0.74–2.17]). Similar results were obtained for the risk of incident TJR. For patients without incident TKR, knee CC did not affect the risk of worsening of K/L grade (odds ratio [OR] 0.9 [95% CI 0.4–1.7]), WOMAC pain subscore (OR 1.1 [95% CI 0.7–1.4]), or WOMAC function subscore (OR 0.9 [95% CI 0.4–2.0]). Conclusion: In patients with symptomatic knee OA, the presence of knee CC did not affect the risk of arthroplasty or disease progression at 5 years.